2014
DOI: 10.1371/journal.pone.0091441
|View full text |Cite
|
Sign up to set email alerts
|

Beamformer Source Analysis and Connectivity on Concurrent EEG and MEG Data during Voluntary Movements

Abstract: Electroencephalography (EEG) and magnetoencephalography (MEG) are the two modalities for measuring neuronal dynamics at a millisecond temporal resolution. Different source analysis methods, to locate the dipoles in the brain from which these dynamics originate, have been readily applied to both modalities alone. However, direct comparisons and possible advantages of combining both modalities have rarely been assessed during voluntary movements using coherent source analysis. In the present study, the cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 71 publications
(84 reference statements)
2
35
0
Order By: Relevance
“…Notwithstanding the fact that a stronger involvement of the cortico-striatal network may have been undetected in our study, our results are consistent with [Tam as Kincses et al, 2008] who did not find correlated activity with the striatum in the early learning phase. Finally, although the ability of MEG to detect subcortical and cerebellar activity is a matter of debate, an increasing number of MEG studies have reported task-related activity modulation at the cerebellum [Bourguignon et al, 2013;Jerbi et al, 2007;Martin et al, 2006;Muthuraman et al, 2014;Stancak et al, 2011] and the caudate nucleus [Altamura et al, 2014], which supports the present rsFC findings.…”
Section: Discussionsupporting
confidence: 88%
“…Notwithstanding the fact that a stronger involvement of the cortico-striatal network may have been undetected in our study, our results are consistent with [Tam as Kincses et al, 2008] who did not find correlated activity with the striatum in the early learning phase. Finally, although the ability of MEG to detect subcortical and cerebellar activity is a matter of debate, an increasing number of MEG studies have reported task-related activity modulation at the cerebellum [Bourguignon et al, 2013;Jerbi et al, 2007;Martin et al, 2006;Muthuraman et al, 2014;Stancak et al, 2011] and the caudate nucleus [Altamura et al, 2014], which supports the present rsFC findings.…”
Section: Discussionsupporting
confidence: 88%
“…Despite this, a direct comparison of the differences between these modalities has yet to be systematically performed. Moreover, the disadvantages of EEG and MEG may be compensated for by utilizing a combination of both modalities, as demonstrated in a number of studies [ 4 15 ]. To the best of our knowledge, no previous studies have shown whether the integration of EEG and MEG data can improve the analysis of spectral power, functional and effective connectivity, and RPR.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the sources to be considered were defined by a regular 3D grid with a 5 mm resolution, thereby creating 3D voxels of 5 mm 3 . As beamforming techniques have been found to be ineffective for reliably reconstructing deep sources of EEG signals measured at the scalp (Muthuraman et al, 2014), only grid points located in the cortex were included in the source reconstruction analysis. Whether grid points were located in cortical areas or not was determined using the AAL atlas developed by (Tzourio-Mazoyer et al, 2002).…”
Section: Methodsmentioning
confidence: 99%